The list of things that will not change eaudiobook - Stead, Rebecca (Listening Library, 2020)
EIGHT STARRED REVIEWS! The reassuring book kids and families need right now. "An absolute original . . . a story that kids will love." —R. J. Palacio, bestselling author of Wonder At a time when everything is changing for Bea and her family, the important things will always stay the same. A soon-to-be classic by the Newbery Award-winning author of When You Reach Me. After her parents' divorce, Bea's life became different in many ways. But she can always look back at the list she keeps in her green notebook to remember the things that will stay the same. The first and most important: Mom and Dad will always love Bea, and each other. When Dad tells Bea that he and his boyfriend, Jesse, are getting married, Bea is thrilled. Bea loves Jesse, and when he and Dad get married, she'll finally (finally!) have what she's always wanted—a sister. Even though she's never met Jesse's daughter, Sonia, Bea is sure that they'll be "just like sisters anywhere." As the wedding day approaches, Bea will learn that making a new family brings questions, surprises, and joy, and readers will discover why the New York Times called Rebecca Stead a "writer of great feeling." "An undeniably beautiful book." — The New York Times "No author writing today observes young lives with more clarity, tenderness, and grace." —Newbery Medalist Katherine Applegate, author of The One and Only Ivan "Stead truly understands the inner life of kids." —Newbery Medalist Erin Entrada Kelly, author of Hello, Universe and You Go First